Sp1 Contributes to Radioresistance of Cervical Cancer Through Targeting G2/M Cell Cycle Checkpoint CDK1 [Corrigendum] - Deng YR (Dove Medical Press, 2021)
Deng YR, Chen XJ, Chen W, et al. Cancer Manag Res. 2019;11:5835–5844. The authors have advised due to an error at the time of figure assembly, Figure 3A on page 5840 is incorrect. The correct Figure 3 is shown in Download Article. The authors apologize for this error and advise it does not affect the results of the paper. Read the original article